High frequency synchronous acquisition and edge computing based electrical topology discovery in low voltage distribution network - Xin LU; Anhui LENG; Shanshan MAO; Haimin HONG; Chun WANG (Dianxin kexue)
Firstly,the current status of electrical topology discovery in low voltage distribution network was introduced,and then the high frequency synchronous acquisition and edge computing based electrical topology discovery in low voltage distribution network was proposed,including high-frequency synchronous data acquisition,Pearson correlation coefficient method for station area identification,analysis of mutual information between electric meters,generation of physical topology through spanning tree algorithm,and so on.Compared with other methods using pure software algorithm to realize topology discovery,the proposed method can not only ensure the simultaneity of data,but also reflect the changes of topology in time,which makes the judgment of electrical topology of low-voltage stations more accurate.